Hubungan Ganguan Akibat Kekurangan Yodium (GAKY) dengan Prestasi Belajar di SDN Tanggalrejo Kecamatan Mojoagung Kabupaten Jombang - Diah Ayu Pitaloka; Mamik Ratnawati; Ida Nikmatul Ulfa (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
The Correlation Of  Iodine Deficiency Disorder  (IDD) With  Learning Achievement  At Public Ementary School ( Sdn  ) Tanggalrejo Village ,  Mojoagung  Sud District , In Jombang District. One nutritional problem In indonesia is IDD.  IDD is known to  be able to effect  abnormality such as mumps, cretin, intelligence disorder,  mental disorder  and physical development disorder that affect  the quality of HR (Human Resources). Impaired intelegence of child, make the child will have difficulty to achieve  learning. The research aimed  to understand  the correlation of IDD with  learning  achievement  at  ( SDN )  Tanggalrejo  Village, Mojoagung Sub district in  Jombang District. This research  was  an analytic correlation with cross sectional approach. The  population as much as 54 respondent was  the   students of   grade 3  at Public Elementary school ( SDN  ) Tanggalrejo  Village Mojoagung sub district in  Jombang  District , and total of  samples was   54 respondents  with the  technique of sampling  used  total sampling. The independent variable  was  Iodine  deficiency  Disorders(IDD) and the dependent variable  was learning achievement with the instrument in the form of inspection and palpation of  thyroid gland and documentation of the value  with   Spearman rank test. The results showed that the most  (70.4%) IDD was  0 degrees  and the most  (33.3%) learning achievement was less , it  was obtained  r value  = 0.351, ρ = 0.009 and ɑ = 0.05, because ρ <ɑ then Ho  was  refused  it meant  there  was  correlation  of IDD with grade 3  student ‘s achievement  at    Public Elementary School  (SDN ) Tanggalrejo  Village , Mojoagung Sub district in  Jombang District.Based on the description above, so that the increase of  iodized salt consumption is needed by  school-age children to prevent the emergence of new problems, and as a correction for people  with  IDD. And necessary counceling about the important iodized salt to community. Keywords: IDD, Learning Achievement